John and Elaine Steinbeck with Friends - unknown:::Creator::::::::::::
From left to right: Mary Dekker, John's sister, Elaine Steinbeck, John Steinbeck, and Michel Tasherean sitting at a table aboard MV Saturnia, part of Societe di navigazione Italia (Italian Line.) Original in safe